Language Attitudes toward English Loanwords in Youth Digital Communication and Their Impact on Academic Achievement - Hoffmann, Alexander (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2013)
In multilingual Libya, English loanwords increasingly permeate youth digital communication on social media and messaging apps, reflecting globalized influences amid Amharic dominance and English-medium education. Language attitudes toward these borrowings shape hybrid practices, yet their dimensions and behavioral links remain underexplored in African contexts. This study investigated Libyan youth's attitudes toward English loanwords in digital communication and their association with usage frequency, identifying underlying attitudinal dimensions and demographic patterns. A survey of 410 urban youth (high school and university students, aged 16–24) employed a Likert-scale questionnaire on attitudes and self-reported loanword use across platforms. Exploratory factor analysis (promax rotation) extracted dimensions, supplemented by descriptive statistics, correlations, and regression. Attitudes were predominantly positive (75.9%), driven by perceptions of modernity, integration, and prestige, with low purism. Factor analysis revealed three robust dimensions: Prestige (symbolic status), Integration (pragmatic utility), and Purism (identity preservation), explaining 84.9% variance. Loanword use was frequent in informal platforms (messaging M=4.31, social media M=4.10) but rare in academic writing (M=2.27). No significant differences emerged by gender, educational level, or age, and attitude factors showed weak, non-significant correlations with use frequency (r<0.07; regression coefficients near zero). English loanwords function as pragmatic, identity-enhancing resources in Libyan youth digital discourse, with pragmatic acceptance dominating over ideological resistance.